Faktor yang Mempengaruhi Minat Peserta Didik dalam Mengikuti Layanan Konseling Perorangan di MTsN Model Padang - Hamida, Hamida; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2014)
This research start from the phenomenon of students who have low motivation in following individual counseling cervice either internal or external. It signed by the unfunctional of counseling room, the students are afraid for coming to counseling room because usually the students who comes there is naughty students or the students who have a problem whether with the teacher or their friends, beside for coming to counseling room the students have to walk front of the teacher office and vice of head master, so the conversation inside of counseling room can hear by the people outside. Moreover the students never come to the counseling room based on their teacher recomendation, their teacher subject and those who has more than three time. The purposes of this research are to describe about 1) the internal factor which influence the students interest in following individual counseling. 2) the external factor which influence students interest in following individual counseling. The research design of this research is descriptive research. The population of this research are all of students in MTsN Model Padang about 1364 students. This research using stratified random sampling in taking a sample, the sample of this research are 93 students. The instrument of this research is questionnaire. Furthermore for data analysis the research using percentage technique. The result of this research find that factor internal which influence students interest in following individual counseling is 60,22% (F=56) in many criteria and the external factor which influence students interest in following individual counseling is 75,27% (F=70) in many criteria. Based on the result above we can conclude that many factors which are influence students interest would make students motivation in following individual counseling is higher